2010
DOI: 10.3233/jad-2010-100684
|View full text |Cite
|
Sign up to set email alerts
|

Oren-gedoku-to and its Constituents with Therapeutic Potential in Alzheimer's Disease Inhibit Indoleamine 2, 3-Dioxygenase Activity In Vitro

Abstract: A well-known traditional Chinese medicinal prescription, Oren-gedoku-to (OGT), has been used in clinical therapies for many types of dementia in China and Japan. Additionally, it ameliorates the age-related deterioration of learning and memory in an Alzheimer's disease (AD) rat model. Indoleamine 2, 3-dioxygenase (IDO-1) is the first and rate-limiting enzyme in the kynurenine pathway of tryptophan catabolism, which ultimately leads to the production of the excitotoxin quinolinic acid (QUIN). IDO-1 has recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 40 publications
0
55
0
1
Order By: Relevance
“…Further evidence supporting the neuroprotective potential of TDO/IDO inhibition has been observed with the compound coptisine -the main active component of the Chinese prescription medication Oren-gedoku-to (OGT) -which is a potent inhibitor of IDO1 [92]. Indeed, treatment of an AD mammalian cell model with coptisine A increased viability while reversing the raised activity of IDO1.…”
Section: Targeting Tdo/ido In Neurodegenerative Diseasementioning
confidence: 96%
“…Further evidence supporting the neuroprotective potential of TDO/IDO inhibition has been observed with the compound coptisine -the main active component of the Chinese prescription medication Oren-gedoku-to (OGT) -which is a potent inhibitor of IDO1 [92]. Indeed, treatment of an AD mammalian cell model with coptisine A increased viability while reversing the raised activity of IDO1.…”
Section: Targeting Tdo/ido In Neurodegenerative Diseasementioning
confidence: 96%
“…Both inhibitors are not available for human use. Berberine, isoquinoline alkaloid isolated from Berberis aristata , a major herb widely used in Indian and Chinese systems of medicine, is a strong inhibitor of the rate-limiting enzyme of TRP-KYN metabolism [7]. We suggested that berberine (as an inhibitor of KYN formation from TRP) might prolong the life span.…”
Section: Introductionmentioning
confidence: 99%
“…It is also found to reduce neutrophil infiltration (Hwang et al, 2002) and suppress preadipocyte differentiation (Ikarashi et al, 2012). These actions rendered possibility of the decoction in treating various diseases including acute gastric mucosal lesions, liver injury, colitis, hypercholesterolemia, transient cerebral ischemia, allergic dermatitis and Alzheimer's disease (Gao et al, 2005;Ohta et al, 1999;Ohta et al, 1997;Sekiya et al, 2005;Xu et al, 2000;Yu et al, 2010;Zhou and Mineshita, 1999). Our clinical observation and review studies also showed that HJLDD has liver protection and anticancer effects and therefore possesses high potential in treatment of liver diseases and cancer (Feng et al, 2008;Tang et al, 2009).…”
Section: Introductionmentioning
confidence: 79%